Preparation method of sodium-based Prussian blue material and sodium-based Prussian blue material
By using potassium ferricyanide, amino acids and organic reducing agents to prepare sodium-based Prussian blue materials, the problem of existing materials being unfavorable to sodium ion deintercalation is solved, and the formation of porous structures and the improvement of sodium-ion battery performance is achieved.
Patent Information
- Application Number
- CN202411654238.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-04
AI Technical Summary
The existing sodium-based Prussian blue material is not conducive to the deintercalation of sodium ions and affects the performance of sodium ion batteries.
Potassium ferrocyanide, amino acids and organic reducing agents were used as raw materials to prepare potassium Prussian blue material by co-precipitation method, and sodium Prussian blue material was obtained through sodium ion exchange. This method is simple, low-cost, and can form a porous structure, which is conducive to sodium deintercalation.
The prepared sodium-based Prussian blue material has a porous structure and is suitable for the positive electrode of sodium-ion batteries, which significantly improves the performance of sodium-ion batteries.
Smart Images

Figure CN119551691A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sodium ion batteries, and specifically provides a preparation method of a sodium-based Prussian blue material and a sodium-based Prussian blue material. Background Art
[0002] In recent years, the demand for electrochemical energy storage, mainly secondary ion batteries, has also greatly increased, but limited lithium resources have restricted the sustainable application of lithium-ion batteries in large-scale energy storage. Sodium-ion batteries are considered to be the best alternative to lithium-ion batteries in the field of electrochemical energy storage due to their abundant sodium resources, low price and wide distribution.
[0003] Sodium-ion batteries and lithium-ion batteries have the same working principles and components. They both store and release electrical energy through the extraction and embedding of ions in positive and negative electrode materials. In the development of sodium-ion battery energy storage devices, finding a suitable positive electrode material is still the core factor affecting the overall performance of the battery. Prussian blue analogs have a three-dimensional open frame structure, can provide a large sodium ion diffusion channel, and have a high specific capacity comparable to commercial lithium iron phosphate, so they have great potential for commercial application.
[0004] The existing sodium-based Prussian blue materials are not conducive to the deintercalation of sodium ions, which affects the performance of sodium-ion batteries.
[0005] Accordingly, this field requires a new technical solution to solve the above technical problems. Summary of the invention
[0006] The present application aims to solve the above technical problem, that is, to solve the problem that the existing Prussian blue material is not conducive to the deintercalation of sodium ions, thereby affecting the performance of sodium ion batteries.
[0007] In a first aspect, the present application provides a method for preparing a sodium-based Prussian blue material, the preparation method comprising the following steps: step S1: providing a mixed solution of potassium ferrocyanide, an amino acid and an organic reducing agent; step S2: reacting the mixed solution in step S1 to generate a potassium-based Prussian blue material; step S3: exchanging sodium ions on the potassium-based Prussian blue material obtained in step S2 to obtain a sodium-based Prussian blue material.
[0008] In the preferred technical scheme of the preparation method of the above-mentioned sodium-based Prussian blue material, step S1 specifically includes dissolving potassium ferrocyanide, amino acid, and the organic reducing agent in a first solvent to obtain a mixed solution; wherein, the first solvent is a mixed solvent of water and an alcohol solvent; and / or, in step S2, the reaction temperature is 25°C to 60°C, and the reaction time is 48h to 96h; and / or, step S3 specifically includes dispersing the potassium-based Prussian blue material obtained in step S2 in water, adding sodium salt for sodium ion exchange, and obtaining a sodium-based Prussian blue material.
[0009] In the preferred technical scheme of the preparation method of the above-mentioned sodium-based Prussian blue material, in the mixed solvent, the volume ratio of the water to the alcohol solvent is water:alcohol solvent=1:(0.33~2); and / or, the water is deionized water; and / or, the alcohol solvent is any one or more of methanol, ethanol or propanol.
[0010] In the preferred technical scheme of the preparation method of the above-mentioned sodium-based Prussian blue material, the sodium salt is sodium chloride or sodium nitrate; and / or the molar ratio of sodium in the sodium salt to potassium in the potassium ferrocyanide is sodium:potassium=(1-2):1.
[0011] In the preferred technical solution of the method for preparing the sodium-based Prussian blue material, the alcohol solvent is methanol.
[0012] In the preferred technical scheme of the preparation method of the above-mentioned sodium-based Prussian blue material, in step S1, the mass ratio of the potassium ferrocyanide, the amino acid and the organic reducing agent is potassium ferrocyanide:amino acid:organic reducing agent=1:(1-2):(1-3).
[0013] In the preferred technical solution of the method for preparing the sodium-based Prussian blue material, in step S1, the mass ratio of the potassium ferrocyanide, the amino acid and the organic reducing agent is potassium ferrocyanide:amino acid:organic reducing agent=1:1.33:2.
[0014] In the preferred technical scheme of the preparation method of the above-mentioned sodium-based Prussian blue material, the amino acid includes at least one of glycine, alanine, valine, leucine, isoleucine, methionine, phenylalanine, proline and tryptophan; and / or the organic reducing agent is any one or more of L-ascorbic acid, VC glucoside, VC ethyl ether, and VC sodium phosphate.
[0015] In a second aspect, the present application provides a sodium-based Prussian blue material, which is prepared by the above-mentioned method for preparing a sodium-based Prussian blue material.
[0016] In the preferred technical solution of the above-mentioned sodium-based Prussian blue material, D50 of the sodium-based Prussian blue material is 500nm~2μm.
[0017] Compared with the prior art, the preparation method of the sodium-based Prussian blue material of the present application has the following beneficial effects:
[0018] The preparation method of the present application uses potassium ferrocyanide, amino acid, and organic reducing agent as raw materials to react to obtain a potassium-based Prussian blue material, and then exchanges the potassium-based Prussian blue material for sodium ions to obtain a sodium-based Prussian blue material. The preparation process is simple and the cost is low. The prepared sodium-based Prussian blue material is porous, which is conducive to sodium deintercalation. The application in the positive electrode of a sodium ion battery can effectively improve the performance of the sodium ion battery.
[0019] In addition, by reacting potassium ferrocyanide, amino acid and organic reducing agent in a mixed solvent of water and alcohol solvent, and controlling the volume ratio of water to alcohol solvent to be water:alcohol solvent=1:(0.33-2), a spherical or quasi-spherical potassium-based Prussian blue material can be obtained, and finally a spherical or quasi-spherical sodium-based Prussian blue material can be obtained. The sodium-based Prussian blue material with this morphology is convenient for homogenous slurry coating when preparing the positive electrode sheet, which can further improve the performance of the sodium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The preferred embodiments of the present application are described below in conjunction with the accompanying drawings, in which:
[0021] Figure 1 is an electron microscope scanning image of Example 1 of the sodium-based Prussian blue material of the present application;
[0022] Figure 2 is an electron microscope scanning image of Example 2 of the sodium-based Prussian blue material of the present application;
[0023] Figure 3 is an electron microscope scanning image of Example 3 of the sodium-based Prussian blue material of the present application;
[0024] Figure 4 is an electron microscope scanning image of Example 4 of the sodium-based Prussian blue material of the present application;
[0025] Figure 5 is an electron microscope scanning image of Example 5 of the sodium-based Prussian blue material of the present application;
[0026] Figure 6 is an electron microscope scanning image of Example 6 of the sodium-based Prussian blue material of the present application;
[0027] Figure 7 is an electron microscope scanning image of Example 7 of the sodium-based Prussian blue material of the present application;
[0028] Figure 8 is an electron microscope scanning image of Example 8 of the sodium-based Prussian blue material of the present application;
[0029] Fig. 9 is an electron microscope scanning image of Example 9 of the sodium-based Prussian blue material of the present application;
[0030] Fig.10 is an electron microscope scanning image of Example 10 of the sodium-based Prussian blue material of the present application;
[0031] Fig.11 is an electron microscope scanning image of Example 11 of the sodium-based Prussian blue material of the present application;
[0032] Fig.12 is an electron microscope scanning image of Example 12 of the sodium-based Prussian blue material of the present application;
[0033] Fig.13 is an electron microscope scanning image of comparative example 1 of the sodium-based Prussian blue material of the present application;
[0034] Fig.14 is an electron microscope scanning image of comparative example 2 of the sodium-based Prussian blue material of the present application;
[0035] Fig.15 is an electron microscope scanning image of comparative example 3 of the sodium-based Prussian blue material of the present application;
[0036] Fig.16 is an electron microscope scanning image of comparative example 4 of the sodium-based Prussian blue material of the present application;
[0037] Fig.17 is an electron microscope scanning image of comparative example 5 of the sodium-based Prussian blue material of the present application;
[0038] Fig.18 This is an electron microscope scanning image of comparative example 6 of the sodium-based Prussian blue material of the present application;. DETAILED DESCRIPTION
[0039] The preferred embodiments of the present application are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present application and are not intended to limit the protection scope of the present application.
[0040] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0041] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0042] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0043] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0044] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0045] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0046] The experimental methods in the following examples are conventional methods unless otherwise specified, and the materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.
[0047] Based on the problem pointed out in the background technology that the existing Prussian blue material is not conducive to the deintercalation of sodium ions, thereby affecting the performance of sodium ion batteries.
[0048] The present application provides a method for preparing a sodium-based Prussian blue material in a first aspect, wherein potassium ferrocyanide, an amino acid, and an organic reducing agent are used as raw materials for reaction to obtain a potassium-based Prussian blue material, and then the potassium-based Prussian blue material is subjected to sodium ion exchange to obtain a sodium-based Prussian blue material. The preparation process is simple and the cost is low, and the prepared sodium-based Prussian blue material is porous, which is conducive to sodium deintercalation. The application of the sodium-based Prussian blue material in the positive electrode of a sodium-ion battery can effectively improve the performance of the sodium-ion battery.
[0049] Specifically, the preparation method of the sodium-based Prussian blue material of the present application comprises the following steps:
[0050] Step S1: providing a mixed solution of potassium ferrocyanide, amino acid and organic reducing agent.
[0051] Step S2: reacting the mixed solution in step S1 to generate potassium-based Prussian blue material.
[0052] Step S3: exchanging the potassium-based Prussian blue material obtained in step S2 with sodium ions to obtain a sodium-based Prussian blue material.
[0053] The present application adopts a simple co-precipitation method to prepare a sodium-based Prussian blue material, utilizes the hydrophobicity of amino acids and the solvent of the mixed solution to form an interfacial reaction, and then utilizes an organic reducing agent for in-situ reduction and etching to obtain a potassium-based Prussian blue material, and then performs sodium ion exchange on the spherical potassium-based Prussian blue material to obtain a sodium-based Prussian blue material. The preparation method is simple and low in cost, and the prepared sodium-based Prussian blue material is porous, which is conducive to the deintercalation of sodium. Its application in the positive electrode can effectively improve the performance of sodium-ion batteries.
[0054] Preferably, step S1 specifically comprises dissolving potassium ferrocyanide, amino acid and the organic reducing agent in a solvent to obtain a mixed solution; wherein the solvent is a mixed solvent of water and an alcohol solvent.
[0055] Potassium ferrocyanide, amino acid and organic reducing agent are reacted in a mixed solvent of water and alcohol solvents to obtain a potassium-based Prussian blue material with a spherical or quasi-spherical morphology, and finally a spherical or quasi-spherical sodium-based Prussian blue material is obtained. The sodium-based Prussian blue material with this morphology is convenient for homogenous slurry coating when preparing a positive electrode sheet, which can further improve the performance of sodium ion batteries. In addition, the preparation method is simple, low-cost, and easy to operate. It does not require calcination, strong acid etching and other violent reactions. Slow etching is performed on the basis of the original cubic Prussian blue, and the original cubic frame does not collapse. The final sodium-based Prussian blue material has small structural distortion and a small unit cell volume.
[0056] It should be noted that the present application does not impose any restrictions on the specific amount of solvent, as long as potassium ferrocyanide, amino acid and organic reducing agent can be completely dissolved in the solvent. In practical applications, technicians in this field can set the amount of solvent according to actual needs.
[0057] Preferably, in the mixed solvent, the volume ratio of water to alcohol solvent is water:alcohol solvent=1:(0.33-2).
[0058] By controlling the volume ratio of water to alcohol solvent in the mixed solvent to water: alcohol solvent = 1: (0.33-2), the morphology of the prepared sodium-based Prussian blue material can be ensured to be regular spherical or quasi-spherical, which can effectively improve the electrochemical performance of sodium ion batteries. If the amount of deionized water in the mixed solvent is too much or too little, the Prussian blue material formed will be cubic, which is not conducive to the formation of spherical or quasi-spherical structures.
[0059] Preferably, the water is deionized water.
[0060] Preferably, the alcohol solvent is any one or more of methanol, ethanol or propanol.
[0061] More preferably, the alcohol solvent is methanol.
[0062] When methanol is selected as the alcohol solvent, it is easier to form a spherical or quasi-spherical sodium-based Prussian blue material with regular morphology.
[0063] It should be noted that the present application does not impose any restrictions on the specific types of amino acids. In practical applications, those skilled in the art can select multiple corresponding amino acid types according to actual needs. For example, the amino acid can be selected as glycine, or the amino acid can be selected as alanine, or the amino acid can be selected as a mixed amino acid of glycine and alanine, etc. The adjustment and change of the specific type of amino acid does not deviate from the basic principles of the present application and should be limited to the scope of protection of the present application.
[0064] Preferably, the amino acid includes at least one of glycine, alanine, valine, leucine, isoleucine, methionine, phenylalanine, proline and tryptophan.
[0065] It should be noted that the present application does not impose any restrictions on the specific types of organic reducing agents. In practical applications, those skilled in the art can select the corresponding types of organic reducing agents according to actual needs. For example, the organic reducing agent can be selected as L-ascorbic acid, or the organic reducing agent can be selected as VC glucoside, or the organic reducing agent can be selected as a mixture of L-ascorbic acid and VC sodium phosphate, etc. The adjustment and change of the specific type of organic reducing agent does not deviate from the basic principles of the present application and should be limited to the protection scope of the present application.
[0066] Preferably, the organic reducing agent is any one or more of L-ascorbic acid, VC glucoside, VC ethyl ether, and VC sodium phosphate.
[0067] More preferably, the organic reducing agent is L-ascorbic acid.
[0068] Preferably, in step S1, the mass ratio of potassium ferrocyanide, amino acid and organic reducing agent is potassium ferrocyanide:amino acid:organic reducing agent=1:(1-2):(1-3).
[0069] Preferably, in step S1, the mass ratio of potassium ferrocyanide, amino acid and organic reducing agent is potassium ferrocyanide:amino acid:organic reducing agent=1:1.33:2.
[0070] By controlling the mass ratio of potassium ferrocyanide, amino acid and organic reducing agent, a Prussian blue material with perfect spherical or quasi-spherical shape can be obtained.
[0071] Preferably, in step S2, the reaction temperature is 25°C to 60°C, and the reaction time is 48h to 96h. Preferably, step S2 is performed in a constant temperature environment, so that the reaction temperature is controlled at a fixed temperature, so as to better control the reaction rate.
[0072] Controlling the reaction temperature at 25°C to 60°C helps control the reaction rate to a certain extent, which is conducive to the organic reducing agent etching the bulk potassium-based Prussian blue material to obtain a porous potassium-based Prussian blue material. In addition, the reaction time is controlled at 48h to 96h, and the reaction time is controlled within a suitable range to obtain a porous methyl Prussian blue material with a suitable particle size, avoiding excessive etching due to a long time, which causes the Prussian blue material to collapse and become extremely small nano-scale particles; it can also avoid the failure to obtain a spherical or quasi-spherical structure of the Prussian blue material due to a short time. Therefore, during the reaction, it is preferred to control the temperature of the constant temperature bath at 25°C to 60°C and the reaction time at 48h to 96h.
[0073] It should be noted that the constant temperature bath described in the present application can be an oil bath or a water bath, as long as the temperature of the constant temperature bath is within an appropriate range. In actual applications, technicians in this field can set the type of constant temperature bath according to actual conditions.
[0074] It should also be noted that, although in the above preferred embodiment, the reaction temperature is controlled at 25°C to 60°C by a constant temperature bath, and the reaction time is controlled at 48h to 96h, this should not limit the protection scope of the present application. In practical applications, the temperature of the constant temperature bath can also be controlled at 20°C, and the reaction time can be appropriately increased, for example, the reaction time is 105h. Alternatively, the time of the constant temperature bath is controlled at 65°C and the reaction time is appropriately reduced; for example, the reaction time is 40h. The adjustment and change of the temperature and reaction time of the constant temperature bath do not deviate from the basic principles of the present application and should be limited within the protection scope of the present application.
[0075] Of course, it is still preferred to set the temperature of the constant temperature bath to 25°C to 60°C and the reaction time to 48h to 96h, and the combination of the two can obtain a spherical or quasi-spherical Prussian blue material with a better etching degree and a better appearance, so as to facilitate homogenization and coating when used. And the temperature of the constant temperature bath is set to 25°C to 60°C and the reaction time is set to 48h to 96h. On the one hand, the reaction time can be shortened as much as possible, so that the Prussian blue material with an ideal morphology can be obtained as soon as possible; on the other hand, the etching quality can be guaranteed as much as possible to avoid the problem of light etching or heavy etching.
[0076] Preferably, step S3 specifically comprises dispersing the potassium-based Prussian blue material obtained in step S2 in water, adding sodium salt to perform sodium ion exchange, and obtaining a sodium-based Prussian blue material.
[0077] It should be noted that the present application does not impose any restrictions on the specific type of sodium salt. In practical applications, those skilled in the art can select the type of sodium salt according to actual needs. For example, the sodium salt can be selected as sodium chloride, or sodium nitrate, or sodium sulfate, etc. The adjustment and change of the specific type of sodium salt does not deviate from the basic principles of the present application and should be limited to the scope of protection of the present application.
[0078] Preferably, the sodium salt is sodium chloride (NaCl) or sodium nitrate (NaNO3).
[0079] Preferably, the molar ratio of sodium in the sodium salt to potassium in potassium ferrocyanide is sodium:potassium=(1-2):1. The molar amount of sodium in the added sodium salt is not less than the molar amount of potassium, and potassium can be completely exchanged during sodium ion exchange, thereby obtaining a sodium-based Prussian blue material with higher purity.
[0080] In a second aspect, the present application further provides a sodium-based Prussian blue material, which is prepared by the preparation method of the sodium-based Prussian blue material provided in the first aspect. The D50 of the sodium-based Prussian blue material is 500nm-2μm.
[0081] The sodium-based Prussian blue material of the present application is described in detail below through several specific embodiments.
[0082] Example 1
[0083] The sodium-based Prussian blue material of this embodiment is prepared by the following steps:
[0084] Step S1: Dissolve 150 g potassium ferrocyanide, 200 g glycine, and 300 g L-ascorbic acid in a mixed solvent of deionized water and methanol, completely dissolve and stir until colorless and transparent to obtain a mixed solution. The volume ratio of deionized water to methanol in the mixed solvent is deionized water: methanol = 3:1.
[0085] Step S2: placing the mixed solution obtained in step S1 in an oil bath for reaction, the oil bath temperature is set to 35° C., the reaction time is 72 h, and a potassium-based Prussian blue material with a D50 of 500 nm is obtained.
[0086] Step S3: The spherical potassium-based Prussian blue material obtained in step S2 is dispersed in deionized water, and 40 g of sodium chloride (NaCl) is added to perform sodium ion exchange to obtain a spherical sodium-based Prussian blue material with a D50 of 500 nm.
[0087] The sodium-based Prussian blue material prepared in this example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Figure 1 The electron microscope scanning image is shown in Table 1. Figure 1 It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment is a spherical structure with a porous and regular morphology.
[0088] Example 2
[0089] The preparation method of the sodium-based Prussian blue material in this embodiment is the same as that in Example 1. The only difference between this embodiment and Example 1 is that the volume ratio of deionized water to methanol in the mixed solvent in step S1 is different. Specifically, in this embodiment, deionized water: methanol = 2:1.
[0090] The sodium-based Prussian blue material prepared in this example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Figure 2 The electron microscope scanning image is shown in Table 1. Figure 2 It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment has a porous spherical structure.
[0091] Example 3
[0092] The preparation method of the sodium-based Prussian blue material in this embodiment is the same as that in Example 1. The only difference between this embodiment and Example 1 is that the volume ratio of deionized water to methanol in the mixed solvent in step S1 is different. Specifically, the mixed solvent in this embodiment is deionized water: methanol = 1:1.
[0093] The sodium-based Prussian blue material prepared in this example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Figure 3 The electron microscope scanning image is shown in Table 1. Figure 3 It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment has a porous spherical structure.
[0094] Example 4
[0095] The preparation method of the sodium-based Prussian blue material in this embodiment is the same as that in Example 1. The only difference between this embodiment and Example 1 is that the volume ratio of deionized water to methanol in the mixed solvent in step S1 is different. Specifically, the mixed solvent in this embodiment is deionized water: methanol = 1:2.
[0096] The sodium-based Prussian blue material prepared in this example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Figure 4 The electron microscope scanning image is shown in Table 1. Figure 4 It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment has a porous spherical structure.
[0097] Example 5
[0098] The preparation method of the sodium-based Prussian blue material in this embodiment is the same as that in Example 1. The only difference between this embodiment and Example 1 is that the amino acid in step S1 is alanine.
[0099] The sodium-based Prussian blue material prepared in this example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Figure 5 The electron microscope scanning image is shown in Table 1. Figure 5 It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment has a porous spherical structure.
[0100] Example 6
[0101] The preparation method of the sodium-based Prussian blue material in this embodiment is the same as that in Example 1. The only difference between this embodiment and Example 1 is that the mass ratios of potassium ferrocyanide, amino acid and L-ascorbic acid in step S1 are different. Specifically, in this embodiment, the masses of potassium ferrocyanide, amino acid and L-ascorbic acid are all 150 g, and potassium ferrocyanide: amino acid: L-ascorbic acid = 1:1:1.
[0102] The sodium-based Prussian blue material prepared in this example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Figure 6 The electron microscope scanning image is shown in Table 1. Figure 6 It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment has a porous spherical structure.
[0103] Example 7
[0104] The preparation method of the sodium-based Prussian blue material in this embodiment is the same as that in Example 1. The only difference between this embodiment and Example 1 is that the mass ratio of potassium ferrocyanide, amino acid and L-ascorbic acid in step S1 is different. Specifically, in this embodiment, the masses of potassium ferrocyanide, amino acid and L-ascorbic acid are 150g, 300g and 450g, respectively, and potassium ferrocyanide: amino acid: L-ascorbic acid = 1:2:3.
[0105] The sodium-based Prussian blue material prepared in this example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Figure 7 The electron microscope scanning image is shown in Table 1. Figure 7 It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment has a porous spherical structure.
[0106] Example 8
[0107] The preparation method of the sodium-based Prussian blue material in this embodiment is the same as that in Example 1. The only difference between this embodiment and Example 1 is the sodium salt added in step S3. Specifically, the sodium salt in this embodiment is sodium nitrate, and the addition amount thereof is 43.1 g.
[0108] The sodium-based Prussian blue material prepared in this example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Figure 8 The electron microscope scanning image is shown in Table 1. Figure 8 It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment is a spherical structure with a porous and regular morphology.
[0109] Example 9
[0110] The preparation method of the sodium-based Prussian blue material in this embodiment is the same as that in Example 1. The difference between this embodiment and Example 1 is only the reaction temperature and reaction time in step S2. Specifically, in this example, the oil bath temperature is set to 25°C and the reaction time is 96h.
[0111] The sodium-based Prussian blue material prepared in this example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Fig. 9 The electron microscope scanning image is shown in Table 1. Fig. 9It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment has a porous spherical structure.
[0112] Example 10
[0113] The preparation method of the sodium-based Prussian blue material in this embodiment is the same as that in Example 1. The difference between this embodiment and Example 1 is only the reaction temperature and reaction time in step S2. Specifically, in this example, the oil bath temperature is set to 60°C and the reaction time is 48h.
[0114] The sodium-based Prussian blue material prepared in this example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Fig.10 The electron microscope scanning image is shown in Table 1. Fig.10 It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment has a porous spherical structure.
[0115] Embodiment 11
[0116] The preparation method of the sodium-based Prussian blue material in this embodiment is the same as that in Example 1. The only difference between this embodiment and Example 1 is the different types of organic reducing agents, the different types of alcohol solvents, and the different amounts of sodium salt added. Specifically, in this embodiment, the organic reducing agent is VC glucoside, the alcohol solvent is propanol, and the amount of sodium chloride added is 26.7 g.
[0117] The sodium-based Prussian blue material prepared in this example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Fig.11 The electron microscope scanning image is shown in Table 1. Fig.11 It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment has a porous spherical structure.
[0118] Example 12
[0119] The preparation method of the sodium-based Prussian blue material in this embodiment is the same as that in Example 1. The only difference between this embodiment and Example 1 is the different types of organic reducing agents, the different types of alcohol solvents, and the different amounts of sodium salt added. Specifically, in this embodiment, the organic reducing agent is sodium VC phosphate, the alcohol solvent is ethanol, and the amount of sodium chloride added is 53.3 g.
[0120] The sodium-based Prussian blue material prepared in this example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Fig.12 The electron microscope scanning image is shown in Table 1. Fig.12 It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment has a porous spherical structure.
[0121] Comparative Example 1
[0122] The sodium-based Prussian blue material of this comparative example is prepared by the following steps:
[0123] Step S1: Dissolve 150 g potassium ferrocyanide, 200 g glycine and 300 g L-ascorbic acid in deionized water, completely dissolve and stir until colorless and transparent to obtain a mixed solution.
[0124] Step S2: placing the mixed solution obtained in step S1 in an oil bath for reaction, setting the oil bath temperature to 35° C., and reacting for 72 hours to obtain a potassium-based Prussian blue material.
[0125] Step S3: Disperse the potassium-based Prussian blue material in step S2 in deionized water, add 40 g of NaCl to perform sodium ion exchange, and obtain a sodium-based Prussian blue material.
[0126] The sodium-based Prussian blue material prepared in this comparative example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Fig.13 The electron microscope scanning image is shown in Table 1. Fig.13 It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment is a block structure.
[0127] Comparative Example 2
[0128] The preparation method of the sodium-based Prussian blue material in this comparative example is the same as that in Example 1. The only difference between this comparative example and Example 1 is that the volume ratio of deionized water to methanol in the mixed solvent in step S1 is different. Specifically, in this example, deionized water: methanol = 4:1.
[0129] The sodium-based Prussian blue material prepared in this comparative example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Fig.14 The electron microscope scanning image is shown in Table 1. Fig.14 It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment is a cubic block structure with holes.
[0130] Comparative Example 3
[0131] The preparation method of the sodium-based Prussian blue material in this comparative example is the same as that in Example 1. The only difference between this comparative example and Example 1 is that the volume ratio of deionized water to methanol in the mixed solvent in step S1 is different. Specifically, in this example, deionized water: methanol = 1:3.
[0132] The sodium-based Prussian blue material prepared in this comparative example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Fig.15 The electron microscope scanning image is shown in Table 1. Fig.15It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment is severely etched in a spherical shape, and the original cubic structure is completely destroyed.
[0133] Comparative Example 4
[0134] The sodium-based Prussian blue material of this comparative example is prepared by the following steps:
[0135] Step S1: Dissolve 150g potassium ferrocyanide and 300g L-ascorbic acid in a mixed solvent of deionized water and methanol, completely dissolve and stir until colorless and transparent to obtain a mixed solution. The volume ratio of deionized water to methanol in the mixed solvent is deionized water: methanol = 3:1.
[0136] Step S2: placing the mixed solution obtained in step S1 in an oil bath for reaction, the oil bath temperature is set to 35° C., and the reaction is carried out for 72 hours to obtain a potassium-based Prussian blue material.
[0137] Step S3: Disperse the potassium-based Prussian blue material in step S2 in deionized water, add 40 g of NaCl to perform sodium ion exchange, and obtain a sodium-based Prussian blue material.
[0138] The sodium-based Prussian blue material prepared in this comparative example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Fig.16 The electron microscope scanning image is shown in Table 1. Fig.16 It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment has a cubic block structure.
[0139] Comparative Example 5
[0140] The sodium-based Prussian blue material of this comparative example is prepared by the following steps:
[0141] Step S1: Dissolve 150g potassium ferrocyanide and 200g glycine in a mixture of deionized water and methanol, completely dissolve and stir until colorless and transparent to obtain a mixed solution, wherein the volume ratio of deionized water to methanol in the mixed solvent is deionized water:methanol=3:1.
[0142] Step S2: placing the mixed solution obtained in step S1 in an oil bath for reaction, the oil bath temperature is set to 35° C., and the reaction is carried out for 72 hours to obtain a potassium-based Prussian blue material.
[0143] Step S3: Disperse the potassium-based Prussian blue material in step S2 in deionized water, add 40 g of NaCl to perform sodium ion exchange, and obtain a sodium-based Prussian blue material.
[0144] The sodium-based Prussian blue material prepared in this comparative example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Fig.17The electron microscope scanning image is shown in Table 1. Fig.17 It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment is a block structure.
[0145] Comparative Example 6
[0146] The sodium-based Prussian blue material of this comparative example is prepared by the following steps:
[0147] Step S1: dissolve 100 g of ferric chloride and 180 g of potassium ferrocyanide in deionized water, completely dissolve and stir until yellow and transparent to obtain a mixed solution.
[0148] Step S2: placing the mixed solution obtained in step S1 in an oil bath for reaction, the oil bath temperature is set to 35° C., and the reaction is carried out for 72 hours to obtain a cubic potassium-based Prussian blue material with a D50 of 1 μm.
[0149] Step S3: The potassium-based Prussian blue material in step S2 is dispersed in deionized water, and 48 g of NaCl is added to perform sodium ion exchange to obtain a cubic sodium-based Prussian blue material with a D50 of 1 μm.
[0150] The sodium-based Prussian blue material prepared in this comparative example was characterized by scanning electron microscopy and particle size characterization, and the following was obtained: Fig.18 The electron microscope scanning image is shown in Table 1. Fig.18 It can be seen from the electron microscope scanning image that the sodium-based Prussian blue material of this embodiment is a block structure.
[0151] Test example
[0152] The sodium-based Prussian blue materials prepared in Examples 1 to 12 and Comparative Examples 1 to 6 were used to prepare sodium ion half-cells. The preparation method of the sodium ion half-cell is as follows: the sodium-based Prussian blue material, Ketjen black and polytetrafluoroethylene emulsion (PTFE, 60wt%) were mixed in a mass ratio of 7:2:1 and then formed into a thin film electrode by a roller press together with a current collector, and then formed into a circular working electrode with a diameter of 12 mm by a slicer, and then the working electrode, glass fiber separator (GF / D, φ=19 mm) and metal sodium sheet (φ=15 mm) were stacked in sequence in a glove box filled with Ar (water oxygen value is less than 1.0 ppm), and then an appropriate amount of 1M NaClO4 ethyl carbonate / diethyl carbonate (EC / DEC) electrolyte containing 2% fluoroethyl carbonate (FEC) was added, and after assembly, it was packaged by a button battery press, and packaged in a CR2032 button battery shell to form a sodium ion half-cell.
[0153] After the assembled sodium ion half-cells were left to stand for 12 hours, the electrochemical performance was tested. The test results are shown in Table 2.
[0154] Table 1 Particle size characterization data of Examples 1 to 12 and Comparative Examples 1 to 6
[0155] Table 2 Electrochemical performance test data of Examples 1 to 12 and Comparative Examples 1 to 6
[0156] From the above experimental data and electron microscope images, we can see that:
[0157] 1. It can be seen from the electron microscope images of Examples 1 to 12 and Comparative Examples 1 to 6 and the data in Table 1 that the D50 of the sodium-based Prussian blue material prepared by the preparation method of the present application is 500 nm to 2 μm, and its surface has a porous structure that is conducive to sodium deintercalation; and from the experimental data in Table 2, it can be seen that the performance of the sodium ion batteries of Examples 1 to 12 and Comparative Examples 2 and 3 is significantly better than that of the sodium ion batteries of Comparative Examples 1 and Comparative Examples 4 to 6; therefore, the sodium-based Prussian blue material prepared by the preparation method of the present application has good performance and can improve the performance of the sodium ion battery when applied to the sodium ion battery.
[0158] 2. From the electron microscope images of Examples 1 to 12 and Comparative Examples 2 and 3 and the data in Tables 1 and 2, it can be seen that by controlling the volume ratio of water to alcohol solvent at water: alcohol solvent = 1: (0.33-2), a spherical or quasi-spherical sodium-based Prussian blue material with good and regular appearance can be obtained, and the performance of the sodium ion batteries of Examples 1 to 12 is better than that of the sodium ion batteries of Comparative Examples 2 and 3. Therefore, it is preferred to make water: alcohol solvent = 1: (0.33-2) to obtain a sodium-based Prussian blue material with better morphology and better performance.
[0159] 3. It can be seen from the electron microscope images of Examples 1 to 12 and Comparative Examples 1 to 6 that only when the raw materials contain amino acids and organic reducing agents at the same time and the solvent of the mixed solution is a mixed solvent of water and alcohol solvents, can a spherical or quasi-spherical sodium-based Prussian blue with a more regular morphology be obtained.
[0160] 4. From the electron microscope images and experimental data of Examples 1, 6 and 7, it can be seen that the morphology of the sodium-based Prussian blue material of Example 1 is more regular, which is a uniform spherical structure, and the performance of the corresponding sodium ion battery is optimal. Therefore, in practical applications, it is preferred that the mass ratio of potassium ferrocyanide, amino acid and organic reducing agent is potassium ferrocyanide: amino acid: organic reducing agent = 1: (1-2): (1-3), and it is most preferred to make potassium ferrocyanide: amino acid: organic reducing agent = 1: 1.33: 2.
[0161] So far, the technical solutions of the present application have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present application is obviously not limited to these specific embodiments. Without departing from the principles of the present application, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present application.
Claims
1. A method for preparing a sodium-based Prussian blue material, characterized in that: The following steps are involved: Step S1: providing a mixed solution of potassium ferrocyanide, amino acid and organic reducing agent; Step S2: reacting the mixed solution in step S1 to generate a potassium-based Prussian blue material; Step S3: exchanging the potassium-based Prussian blue material obtained in step S2 with sodium ions to obtain a sodium-based Prussian blue material.
2. The method for preparing the sodium-based Prussian blue material according to claim 1, characterized in that: Step S1 specifically comprises dissolving potassium ferrocyanide, amino acid and the organic reducing agent in a solvent to obtain a mixed solution; wherein the solvent is a mixed solvent of water and an alcohol solvent; and / or, in step S2, the reaction temperature is 25°C to 60°C, and the reaction time is 48h to 96h; And / or, step S3 specifically includes dispersing the potassium-based Prussian blue material obtained in step S2 in water, adding sodium salt to perform sodium ion exchange, and obtaining a sodium-based Prussian blue material.
3. The method for preparing the sodium-based Prussian blue material according to claim 2, characterized in that: In the mixed solvent, the volume ratio of the water to the alcohol solvent is water:alcohol solvent=1:(0.33-2); And / or, the water is deionized water; And / or, the alcohol solvent is any one or more of methanol, ethanol or propanol.
4. The method for preparing the sodium-based Prussian blue material according to claim 2, characterized in that: The sodium salt is sodium chloride or sodium nitrate; And / or, the molar ratio of sodium in the sodium salt to potassium in the potassium ferrocyanide is sodium:potassium=(1-2):
1.
5. The method for preparing the sodium-based Prussian blue material according to claim 3, characterized in that: The alcohol solvent is methanol.
6. The method for preparing the sodium-based Prussian blue material according to claim 1, characterized in that: In step S1, the mass ratio of the potassium ferrocyanide, the amino acid and the organic reducing agent is potassium ferrocyanide:amino acid:organic reducing agent=1:(1-2):(1-3).
7. The method for preparing the sodium-based Prussian blue material according to claim 6, characterized in that: In step S1, the mass ratio of the potassium ferrocyanide, the amino acid and the organic reducing agent is potassium ferrocyanide:amino acid:organic reducing agent=1:1.33:
2.
8. The method for preparing the sodium-based Prussian blue material according to any one of claims 1 to 7, characterized in that: The amino acids include at least one of glycine, alanine, valine, leucine, isoleucine, methionine, phenylalanine, proline and tryptophan; And / or, the organic reducing agent is any one or more of L-ascorbic acid, VC glucoside, VC ethyl ether, and VC sodium phosphate.
9. A sodium-based Prussian blue material, characterized in that: The sodium-based Prussian blue material is prepared by the preparation method of any one of claims 1 to 8.
10. The sodium-based Prussian blue material according to claim 9, characterized in that: The D50 of the sodium-based Prussian blue material is 500nm-2μm.